Regional Variation of Potential and Actual Labor Resources in Poland in the Light of Forecasts Through 2040 - Majdzińska, Anna (Olsztyn Economic Journal, 2015)
This paper considers the issue of additional retirement security for farmers. On the basis of theoretical considerations and empirical data analysis, the hypothesis is that in the face of a low level of farmers’ pensions, insured persons who would like to guarantee themselves a satisfactory replacement rate must use supplementary retirement security instruments. Studies conducted to test the main objective of the research, which was based on an analysis of current incomes, the level of retirement insurance premiums and pensions for different sized homesteads, confirmed the assumptions expressed in the main hypothesis. As an addition to the main objective of the research, the potential forms of supplementary retirement security and their characteristics were presented.